Application of polymerase chain reaction assay in detection of Leptospira icterohaemorrhagiae in experimentally infected mice - Omar, Sharina; Bejo, Siti Khairani; Bahaman, Abdul Rani (Medwell Online, 2007)
A total of 24 mice were inoculated with 1x107 of Leptospira icterohaemorrhagiae. Four mice as negative control were not inoculated. Four inoculated mice were sacrificed at each sampling day on day 1, 3, 7, 10, 14 and 21 post inoculation. Blood and kidney samples were collected and inoculated into JS medium for isolation of L. icterohaemorrhagiae. Polymerase Chain Reaction (PCR) assay was performed to detect the present of the organisms in blood and kidneys. All culture samples were negative for L. icterohaemorrhagiae. However, one (1/24) blood sample was positive by PCR. It is apparent that detection of leptospires in blood with PCR is a promising approach for early diagnosis of leptospirosis.